Assessing the impact of the influential factors of airport biometric technology on air traveler behavioral intentions in the With-COVID-19 rra: the role of attitude and mental health value - Untaru, Elena Nicoleta; Chi, Xiaoting; Jung, Heekyoung; Chua, Bee Lia; Han, Heesup (Routledge, 2024)
The risk of virus transmission while traveling due to COVID-19 has increased travelers' concerns about the general state of mental health, such as anxiety, depression and psychological distress. Biometric technologies have the potential to enhance passenger mental health, since this technology is contactless, replacing the physical check of travel documents and the close human contact. Therefore, the present study sought to develop a theoretical framework to investigate the impact of influential factors of biometric technology at an airport (i.e., perceived security, perceived convenience and functional value), and perceptions of viral disease risk, on passengers’ mental health, attitudes toward biometric technology, and behavioral intentions. Findings showed that the perceived security and functional value of biometric technology and the perception of viral disease risk influenced passengers’ mental health while perceived security and perceived convenience affected attitudes and behavioral intentions. Mental health was the most significant factor in explaining intentions toward biometric technology.